2015
DOI: 10.1089/scd.2014.0600
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Differentiated from Human Umbilical Cord Blood-Derived Monocytes Exhibit Tolerogenic Characteristics

Abstract: Human umbilical cord blood (UCB) is rich in diverse hematopoietic stem cells that are competent to differentiate into various cell types with immunological compatibility at transplantation. Thus, UCB is a potential source for the preparation of dendritic cells (DCs) to be used for cell therapy against inflammatory disorders or cancers. However, the immunological properties of UCB-derived DCs are not fully characterized. In this study, we investigated the phenotypes and functions of UCB monocyte-derived DCs (UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…CB-derived dendritic cells (DCs) induce weaker T-cell activation and proliferation than DCs derived from adult peripheral blood (PB), 10,11 presumably due to reduced expression of maturation markers, MHC molecules, and their decreased ability to produce cytokines such as IL-12 and tumor necrosis factor (TNF)-a. [10][11][12][13][14] Furthermore, CB T cells are characterized by impaired nuclear factor of activated T cells (NFAT) signaling and reduced reactivity. [15][16][17] Further investigation is needed to gain a thorough understanding of the na€ ıvet e of CB immune cells and the interplay with recipient target T cells in the context of GVHD and GVT effects.Studies reporting the successful stimulation and activation of antigen-specific CD41 T-helper and cytotoxic CD81 T lymphocytes (CTLs) from CB using autologous lymphoblastoid cell lines (LCLs) 18 or CB-derived DCs for antigen presentation 19 are scarce.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CB-derived dendritic cells (DCs) induce weaker T-cell activation and proliferation than DCs derived from adult peripheral blood (PB), 10,11 presumably due to reduced expression of maturation markers, MHC molecules, and their decreased ability to produce cytokines such as IL-12 and tumor necrosis factor (TNF)-a. [10][11][12][13][14] Furthermore, CB T cells are characterized by impaired nuclear factor of activated T cells (NFAT) signaling and reduced reactivity. [15][16][17] Further investigation is needed to gain a thorough understanding of the na€ ıvet e of CB immune cells and the interplay with recipient target T cells in the context of GVHD and GVT effects.Studies reporting the successful stimulation and activation of antigen-specific CD41 T-helper and cytotoxic CD81 T lymphocytes (CTLs) from CB using autologous lymphoblastoid cell lines (LCLs) 18 or CB-derived DCs for antigen presentation 19 are scarce.…”
mentioning
confidence: 99%
“…[2][3][4] The unique antigen-na€ ıve status of T cells from CB (CB T cells) is likely responsible for the decreased alloreactivity of CB grafts. CB-derived dendritic cells (DCs) induce weaker T-cell activation and proliferation than DCs derived from adult peripheral blood (PB), 10,11 presumably due to reduced expression of maturation markers, MHC molecules, and their decreased ability to produce cytokines such as IL-12 and tumor necrosis factor (TNF)-a. [10][11][12][13][14] Furthermore, CB T cells are characterized by impaired nuclear factor of activated T cells (NFAT) signaling and reduced reactivity.…”
mentioning
confidence: 99%
“…22,23 Our DCs, which were generated from umbilical cord blood monocytes, had characteristics similar to the DCs that were generated from peripheral blood monocytes such as long dendrites, and high expression of DC surface marker profile including CD80high, CD86high, CD40high, HLA-DRhigh. [30][31][32][33][34] In addition, DCs in this current study also expressed CD14high and CD56high, which are the 2 markers of monocytes. Nidea et al (2015) also reported that DCs obtained from IFN-a-induced monocytes still kept these 2 markers on their surface.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have reported that the cord blood monocyte-derived DCs have the typical size and morphology of DCs, and express multiple DC makers. 32,33 We followed the protocol developed by Paquette et al (1998) and Nidea et al (2015), in which DCs were generated in vitro from monocyte of peripheral blood by inducing them with IFN-a. 22,23 Our DCs, which were generated from umbilical cord blood monocytes, had characteristics similar to the DCs that were generated from peripheral blood monocytes such as long dendrites, and high expression of DC surface marker profile including CD80high, CD86high, CD40high, HLA-DRhigh.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments using human blood were conducted under the approval of the Institutional Review Board of Seoul National University. The peripheral blood was diluted in phosphate-buffered saline (PBS) and overlaid on the Ficoll-Paque PLUS, and peripheral blood mononuclear cells (PBMCs) were isolated by density-gradient centrifugation as previously described ( 16 , 17 ). PBMCs were washed with PBS three times to remove platelets and the remaining Ficoll.…”
Section: Methodsmentioning
confidence: 99%